Challenges in School Management and Supervision: Insights from Educators in Chinese Colleges - Hou Yi (International Journal of Education and Humanities, 2025)
This study examines the challenges faced by educators in Chinese colleges regarding school management and oversight. It explores teacher demographics, including age, gender, years of experience, and highest educational attainment. The research evaluates the effectiveness of current administrative approaches in leadership development, instructional leadership, cultural awareness, creating a conducive school environment, and resource allocation. While these strategies are generally effective, several areas require further improvement, such as enhancing access to mentoring, fostering curricular collaboration, promoting diversity, improving conflict resolution mechanisms, and ensuring equitable resource distribution. Survey findings reveal no significant differences in assessing these approaches across various demographic groups, indicating a shared perspective among faculty members. However, the study identifies several critical challenges, including bureaucratic constraints, limited professional development opportunities, inadequate funding, the dual burden of teaching and research responsibilities, and a lack of autonomy in curriculum design. The study recommends targeted measures to address these issues, such as expanding access to professional development programs, enhancing administrative flexibility, and ensuring sufficient resources to support curriculum innovation and interfaculty collaboration. These findings aim to guide policymakers and educational administrators in improving the quality of higher education management in China.